2011
DOI: 10.1002/zaac.201100077
|View full text |Cite
|
Sign up to set email alerts
|

Zinc(II) and Mercury(II) Complexes of Pyrazole‐Based NNN‐Type Ligands: Syntheses, X‐ray Structures, Thermal Analyses and DFT Studies

Abstract: Monomeric zinc(II) and mercury(II) complexes containing tripodal nitrogen donor ligand 2,6-bis(3,4,5-trimethyl-N-pyrazolyl)pyridine (btmpp) were synthesized, and characterized by elemental and spectroscopic (IR, UV/Vis) analyses, TG-DTA and single-crystal Xray diffraction studies. X-ray analyses of the complexes [Zn(btmpp)Cl 2 ] (2) and [Hg(btmpp)(SCN) 2 ] (3) showed that both structures crystallize in space group P2 1 /c with a = 7.9722(6), b = 18.3084(13), c = 13.3117(9) Å and Z = 4 for 2 and a = 8.7830(3), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…In addition to those already discussed, many other complexes of 1-bpp and 3-bpp derivatives have been characterised since 2005. 6 Most of these are adducts of 1-bpp derivatives with divalent metal salts from groups 8, 14,169,170,175 [186][187][188][189][190][191][192] although individual titanium(IV), 193 iron(III) 15 and rhenium(I) 194 examples are also included. An IR study showed that L 34 forms adducts in methanol solution with CuCl 2 , NiCl 2 and CoCl 2 , but not with MgCl 2 or CaCl 2 .…”
Section: Other Complexesmentioning
confidence: 99%
“…In addition to those already discussed, many other complexes of 1-bpp and 3-bpp derivatives have been characterised since 2005. 6 Most of these are adducts of 1-bpp derivatives with divalent metal salts from groups 8, 14,169,170,175 [186][187][188][189][190][191][192] although individual titanium(IV), 193 iron(III) 15 and rhenium(I) 194 examples are also included. An IR study showed that L 34 forms adducts in methanol solution with CuCl 2 , NiCl 2 and CoCl 2 , but not with MgCl 2 or CaCl 2 .…”
Section: Other Complexesmentioning
confidence: 99%
“…Despite the potentially energetic nature of these molecules the authors report no success in effecting explosive decomposition. The simple oxidative addition of diiodide adducts of methimazole (MeImSH) and propylthiouracil (PTU) to elemental mercury have been described, 57 58 The mononuclear coordination chemistry of mercury with a variety of pincer type ligands has also been described, 59,60 as have a novel series of complexes based on the ferrocene-pyridylphosphine ligands [Fc(1-PPh 3 )(1 0 -py 0 )] (py 0 = 2-py, 3-py, CH 2 -2-py), which exhibit both mononuclear k 2 -N,P and dimeric k-P 2 coordination modes, depending on the particular combination of ligand and halide. 61 Finally, selenoate complexes [Hg(SeC 5 H 4 N) 2 (tmeda)] and [Hg(SeC 5 H 3 (Me-3)N) 2 ] have been show to form HgSe upon thermolysis, in admixture with mercury and further selenide decomposition products (cf.…”
Section: Mercurymentioning
confidence: 99%
“…mercury complexes involving HgN 3 S 2 chromophores and distorted square pyramidal geometry is 140.84(9) and 126.09(7) in C 24 H 26 Hg 2 N 10 S 4 and 143.0(2) and 125.70(15) in C 19 H 21 HgN 7 S 2 52,53. The comparison of bond lengths in the two present complexes indicates that the Hg-N amine bond length in both complexes is shorter than Hg-N imine and moreover, Hg-N imine bond lengths in HgL(SCN) 2 complex (Hg1-N2 ¼ 2.455(14) Å and Hg1-N4 ¼ 2.433(14) Å) are shorter than them values in HgLI 2 complex (Hg-N2 ¼ 2.618(10) Å and Hg-N4 ¼ 2.610(10) Å).…”
mentioning
confidence: 99%